Gestão da informação para a responsabilidade socioambiental nos meios de hospedagem de Sergipe - Valença, Kleber Firpo Prado (2021)
Information Science has as a study bias the process of communication and information that can be developed in various areas of knowledge, including Tourism, which over the years has been developing and gaining space in the scenario of the world and national economy, being It is necessary to look for managements that assume social and environmental responsibility in their projects, seeking to mitigate the impacts caused by the use of environmental and social resources. This research aimed to observe the constant growth in the tourism and hotel sector in northeastern Brazil, mainly in the State of Sergipe, sought to analyze, through a qualitative-quantitative study in the “Costa dos Coqueirais” and “Velho Chico” Poles, how they are developed in the daily lives of means of accommodation the work activities of employees and guests, through the study of social and environmental responsibility. Thus, the hypothetical-deductive method was used, which provided the analysis of social and environmental responsibility practices collected through a questionnaire, based on information obtained by the managers of a hotel in Aracaju. Based on the concept of socio-environmental responsibility and its relationship with tourism, the research sought to raise the potential and challenges in relation to energy efficiency, water, solid waste, social and information indicators found in eleven hotels in the region in the search for sustainable development, through the creation and the Manual of Environmental Sustainability in Accommodation Environment. As a result, it is expected that the means of accommodation in Aracaju, adopt the actions of the Manual and with the application of the "Environmental Manual of the Means of Accommodation in Sergipe", the final product of this research, thus promoting sustainable environmental and social practices in the hotel industry in Sergipe.